Obtención de biodiesel a partir de aceite de omphalea diandra - Souza Nájar, Rosa Isabel (2017)
The objective of this study was to create biodiesel obtained from oil of almonds Omphales diandra, by transesterification of methanol under basic conditions using sodium hydroxide as catalyst. The oil extraction was performed by the extraction method soxhelet having a yield 42.83%, an acid number of 0.80 mg KOH / g of oil and 0.40% of fatty acids and by the cold pressing method yielding 6.8%, an acid number of 1.26 mg KOH / g of oil and 0.64% of fatty acids respectively. The transesterification reaction was carried out at laboratory scale in a batch Pyrex glass reactor with agitation of 400 rpm; with reflux condensation and a temperature of 60 ° C. It was performed, a design of experiments on three factors at two levels. The variables analyzed in this study were: the molar ratio oil/alcohol (1/6 and 1/9) reaction time (30 min and 60 min) and quantity of catalyst (0.5% and 1% by weight of the oil), taking as base oil used in order to quantify their influence on process performance. The higher conversion to biodiesel was 86.14% at a molar ratio oil/alcohol 6/1, reaction time 30 minutes, a percentage of 0.5% catalyst and 60 ° C. Se characterized biodiesel obtained by evaluating their characteristics physical as density (0.877g / cm3), viscosity (5.4 mm2 / s) and content of fatty acid methyl esters (FAME) of 112.31% .The results were compared with the technical specifications, concluding that biodiesel was obtained compliant with the provisions of these rules that can help reduce the environmental impact and growing demand for fossil fuels.